KARAKTERITIK BETON ASPAL LAPIS PENGIKAT (AC-BC) YANG MENGGUNAKAN BAHAN PENGISI PENGISI (FILLER) ABU SEKAM PADI - Ismadarni, Ismadarni; Risman, Risman; Kasan, Muhammad (MEKTEK, 2013)
Asphalt Concrete Binder Course (AC-BC) Pavement is a type of asphalt pavement located between base layer and wearing course. The study was conducted describing the the effect of the use of rice husk ash onthe characteristics of asphalt concrete AC-BC mixtures. The purpose of this study was to determine thecharacteristics of the asphalt concrete binder course mixtures (AC-BC) which uses rice husk ash as filler,determine the optimum percentage of rice husk filler in AC-BC pavement mixtures. Research materials include coarse aggregate, fine aggregate and rice husk ash. Coarse and fine aggregateobtained from Stone Cruiser of Taipa and Palu River, while rice husk ash obtained fromBiromaru area in Sigi Regency. Asphalt used in this study is Asphalt pen. 60/70 produced by Pertamina.Investigation and testing of these materials has been carried out in the Laboratory of Transportation andHighways, Department of Civil Tadulako University of Palu.Research has been carried out by using rice husk ash filler variation of 0%, 25% and 50%. The datacollected includes characteristics of volumetric and Marshall test characteristics of AC-BC pavementmixture on each rice husk ash content. The data include density, VIM, VMA, VFB, Stability, flow, MarshallQuotient value and residual stability of the mixture. The data is processed and displayed in graphical form, then do a comparative analysis between the characteristics of the AC-BC mixture that uses rice husk ash andwithout rice husk ash.The results of the study found that increasing the percentage of rice husk ash content in the mix AC-BC tendsto increase the use of bitumen content. It can be seen from the increasing value of Optimum Bitumen Content(OBC) on rice husk ash variation of 0% - 50%. The results also gain an increase in the durability of the ACBCmixtureofricehuskashonthevariationof0%- 5%asindicatedbytheincreasedtheresidualstabilityvalueofthe AC-BC pavementmixtures.Maximum stabilityoccursinrice huskashcontentof25%.Keywords: Asphalt Concrete Binder Course (AC-BC), rice husk ash